Knowledge Management: Case Studies in SMEs and Evaluation of an Integrated Approach - Wong, K. Y.; Aspinwall, E. (World Scientific, 2005)

(untitled)
To date, very few publications have been found that describe how small and medium enterprises (SMEs) are adopting knowledge management (KM). The same is true concerning attempts to develop a framework to help them implement it. To redress this, this paper presents the results of four case studies conducted in UK SMEs to examine their KM implementation effort. In addition, a new integrated framework developed by the authors was evaluated to determine its applicability in this business sector. The methodology employed to conduct the studies is described and each of the cases is then presented. The results are analysed and key lessons or findings gathered from the companies are highlighted. Comments received from the companies with respect to the integrated framework were positive and favourable. It is hoped that the information accrued from the case studies, together with the integrated framework, will help to pave the way for SMEs to accomplish KM.